An ESPGHAN Position Paper on the Use of Low-FODMAP Diet in Pediatric Gastroenterology. Issue 3 (9th August 2022) - Thomassen, R.A.; Luque, V.; Assa, A.; Borrelli, O.; Broekaert, I.; Dolinsek, J.; Martin-de-Carpi, J.; Mas, E.; Miele, E.; Norsa, L.; Ribes-Koninckx, C.; Saccomani, M. Deganello; et al.
Abstract : Excluding oligo-, di-, monosaccharides and polyols (FODMAPs) from the diet is increasingly being used to treat children with gastrointestinal complaints. The aim of this position paper is to review the available evidence on the safety and efficacy of its use in children and provide expert guidance regarding practical aspects in case its use is considered . Members of the Gastroenterology Committee, the Nutrition Committee and the Allied Health Professionals Committee of the European Society for Pediatric Gastroenterology Hepatology and Nutrition contributed to this position paper. Clinical questions regarding initiation, introduction, duration, weaning, monitoring, professional guidance, safety and risks of the diet are addressed. A systematic literature search was performed from 2005 to May 2021 using PubMed, MEDLINE and Cochrane Database of Systematic Reviews. In the absence of evidence, recommendations reflect the expert opinion of the authors. The systematic literature search revealed that the low-FODMAP diet has not been comprehensively studied in children. Indications and contraindications of the use of the diet in different pediatric gastroenterological conditions are discussed and practical recommendations are formulated. There is scarce evidence to support the use of a low-FODMAP diet in children with Irritable Bowel Syndrome and no evidence to recommend its use in other gastrointestinal diseases and complaints in children. Awareness of how and when to use the diet is crucial, as a restrictive diet may impact nutritional adequacy and/or promote distorted eating in vulnerable subjects. The present article provides practical safety tips to be applied when the low-FODMAP diet is considered in children.